2019
DOI: 10.1021/acsomega.8b02654
|View full text |Cite
|
Sign up to set email alerts
|

Electronic Effect-Guided, Palladium-Catalyzed Regioselective B–H Activation and Multistep Diarylation of o-Carboranes with Aryl Iodides

Abstract: Density functional theory calculations at IDSCRF-B3LYP/DZVP computational level were conducted on palladium-catalyzed regioselective B–H activation and diarylation of o -carboranes with aryl iodides in solution. Computational results indicate that this reaction follows a multistep mechanism and needs to get over several transition states before the final B(4,5)-diarylated o -carborane derivatives are formed. B–H activation, oxidation addition, and successive reduct… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
5
1
1

Relationship

1
6

Authors

Journals

citations
Cited by 10 publications
(2 citation statements)
references
References 73 publications
0
2
0
Order By: Relevance
“…[49][50][51][52][53][54][55][56] Usually, introducing a directing group (DG) on o-carborane is a powerful way to manipulate the regioselectivities of these B-H bonds. 27,47,[57][58][59][60][61] In 2014, Xie reported a catalytic B(4)-H alkylation of carboxylic o-carboranes using Cp*IrCl 2 as catalyst. 62 Later, Yan and Lu developed a B(3)-H acetoxylation of pyridyl-modified o-carborane using Cp*RhCl 2 (Scheme 1(b)).…”
Section: Introductionmentioning
confidence: 99%
“…[49][50][51][52][53][54][55][56] Usually, introducing a directing group (DG) on o-carborane is a powerful way to manipulate the regioselectivities of these B-H bonds. 27,47,[57][58][59][60][61] In 2014, Xie reported a catalytic B(4)-H alkylation of carboxylic o-carboranes using Cp*IrCl 2 as catalyst. 62 Later, Yan and Lu developed a B(3)-H acetoxylation of pyridyl-modified o-carborane using Cp*RhCl 2 (Scheme 1(b)).…”
Section: Introductionmentioning
confidence: 99%
“…On the other hand, affected by many factors such as large size of o-carboranyl group, many electrons involved in transition metals, and diverse regioselectivities of o-carborane's B-H activation, it is really challenging in computational cost to conduct theoretical studies on transition metal catalyzed regioselective B-H activation of o-carborane. Our group has recently conducted a computational study on palladium-catalyzed regioselective B-H activation and diarylation of o-carboranes with aryl iodides in solution, and found that the substituents on o-carborane have a significant effect on the regioselectivity of B-H activation [27]. In contrast to this, the presence of a fused five-membered ring in intermediates M2 and M3 (Scheme 1) here would Catalysts 2019, 9,548 3 of 16 affect the regioselectivity of B-H activation significantly, and lead to different diastereoselectivities in the following cage B-C(sp 2 ) coupling through direct B-H activation of o-carborane.…”
Section: Introductionmentioning
confidence: 99%